A critical analysis of the coverage of Uganda's 2000 referendum by The New Vision and The Monitor newspapers - Wakabi, Wairagala (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2003)
On July 29 2000, Uganda held a referendum to decide whether to continue with the ruling Noparty Movement system or to revert to the Multi-party platform. This research entails a qualitative content analysis of the role the media played in driving debate and understanding of the referendum and its role in the country's democratisation process. The research is informed by Jurgen Habermas's public sphere paradigm as well as the sociological theory of news production. The research covers Uganda's two English dailies "“ The New Vision and The Monitor, examining whether they provided a public sphere accessible to all citizens and devoid of ideological hegemony. It concludes that the newspapers were incapable of providing such a sphere because of the structural nature of Ugandan society and the papers' own capitalistic backgrounds and ownership interests. The research concludes that such English language newspapers published in a country with a low literacy rate and low income levels, can only provide a public sphere to elite and privileged sections of society. A case is then made that multiple public spheres would be better suited to represent the views of diverse interest groups.
Keywords: National Resistance Movement (Uganda); New Vision (Uganda); Monitor (Uganda); Democracy -- Uganda; Political participation -- Uganda; Mass media -- Political aspects -- Uganda; Press and politics -- Uganda; Freedom of the press -- Uganda; Uganda -- Politics and government -- 1979-